Evidence of a Role for the TRPC Subfamily in Mediating Oxidative Stress in Parkinson’s Disease - Maria-Ferreira, Daniele; de Oliveira, Natalia Mulinari Turin; da Silva, Liziane Cristine Malaquias; Fernandes, Elizabeth Soares (Frontiers in Physiology, 2020)
Parkinson’s disease (PD) represents one of the most common multifactorial neurodegenerative disorders affecting the elderly population. It is associated with the aggregation of α-synuclein protein and the loss of dopaminergic neurons in the substantia nigra pars compacta of the brain. The disease is mainly represented by motor symptoms, such as resting tremors, postural instability, rigidity, and bradykinesia, that develop slowly over time. Parkinson’s disease can also manifest as disturbances in non-motor functions. Although the pathology of PD has not yet been fully understood, it has been suggested that the disruption of the cellular redox status may contribute to cellular oxidative stress and, thus, to cell death. The generation of reactive oxygen species and reactive nitrogen intermediates, as well as the dysfunction of dopamine metabolism, play important roles in the degeneration of dopaminergic neurons. In this context, the transient receptor potential channel canonical (TRPC) sub-family plays an important role in neuronal degeneration. Additionally, PD gene products, including DJ-1, SNCA, UCH-L1, PINK-1, and Parkin, also interfere with mitochondrial function leading to reactive oxygen species production and dopaminergic neuronal vulnerability to oxidative stress. Herein, we discuss the interplay between these various biochemical and molecular events that ultimately lead to dopaminergic signaling disruption, highlighting the recently identified roles of TRPC in PD.